Palembang jumputan textile as cultural heritage: a historical study and its development dynamics - Mukhsin Patriansah; I Ketut Muka; Nyoman Dewi Pebryani; Tjok Istri Ratna C.S (Gelar: Jurnal Seni Budaya, 2026)
An analysis of its developmental dynamics over time. The research aims to trace the historical existence of jumputanfabric and investigate its development across different historical periods, ranging from the Srivijaya era and the Palembang Sultanate to the contemporary period. The novelty of this study lies in its effort to systematically explore the historical trajectory and developmental dynamics of Palembang jumputan fabric, thereby revealing not only its origins and evolution but also the transformation of its functions, motifs, techniques, and cultural meanings amid social changes in Palembang society. The theoretical contribution of this research is the strengthening of historical and cultural heritage studies through an analysis of the development of Palembang jumputan fabric as a cultural artifact that reflects historical values and the continuity of cultural identity in the face of changing times. This research employs a qualitative method with a historical approach through literature review, document analysis, interviews, and the interpretation of other relevant sources. The research was conducted at the Bumiayu Temple Site in Penukal Abab Lematang Ilir (PALI) Regency, South Sumatra, the Balaputradewa Museum, the Sultan Mahmud Badaruddin II Museum, and the Tuan Kentang Weaving Village in Palembang. Data analysis was carried out through the stages of data identification, data reduction, data analysis, and synthesis. The findings reveal that visual representations resembling jumputan fabric can be identified on the statues of deities and Shiva located at the Bumiayu Temple Site in PALI Regency, South Sumatra. Furthermore, the results demonstrate significant developmental dynamics of Palembang jumputan fabric in terms of technical innovation, motif forms and patterns, as well as its artistic, aesthetic, and functional values. The study concludes that Palembang jumputan fabric reflects an ongoing process of cultural negotiation between tradition and modernity while simultaneously serving as an important medium for preserving cultural identity in the midst of globalization.